2021
DOI: 10.1177/16878140211028456
|View full text |Cite
|
Sign up to set email alerts
|

Study on performance of thrust disk as auxiliary impeller

Abstract: Thrust disk as auxiliary impeller has a vital effect on the big power pump unit with wet motor. It can balance the axial force of the unit, provide power for internal cooling circulation circuit of motor, and further reduce the axial length of the unit. Due to the motor chamber space is limited, and the transmission medium is liquid which needs to consider the effect of cavitation, the research of thrust disk of auxiliary impeller is different from the previous studies of rotating channel. In this paper, the h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 21 publications
(19 reference statements)
0
1
0
Order By: Relevance
“…The findings highlighted that increasing the inlet pressure and adjusting the operating flow rate to the design value effectively mitigates cavitation. Bai et al [22] investigated the hydraulic performance and anti-cavitation properties of the thrust plate-assisted impeller using experimental methods under different speeds, temperatures, and outlet conditions. The experimental results revealed that the speed variation pattern differs from that of traditional centrifugal pumps and is not applicable to the head produced by the thrust plate-assisted impeller.…”
Section: Introductionmentioning
confidence: 99%
“…The findings highlighted that increasing the inlet pressure and adjusting the operating flow rate to the design value effectively mitigates cavitation. Bai et al [22] investigated the hydraulic performance and anti-cavitation properties of the thrust plate-assisted impeller using experimental methods under different speeds, temperatures, and outlet conditions. The experimental results revealed that the speed variation pattern differs from that of traditional centrifugal pumps and is not applicable to the head produced by the thrust plate-assisted impeller.…”
Section: Introductionmentioning
confidence: 99%